Current pharmacological and surgical treatment of underactive bladder - Yuan-Hong Jiang; Cheng-Ling Lee; Jia-Fong Jhang; Hann-Chorng Kuo (Tzu-Chi Medical Journal, 2017)
Underactive bladder (UAB) or detrusor underactivity (DU) is a common yet still poorly understood urological problem. In addition to true detrusor failure and neuropathy, the inhibitory effects of detrusor contraction by the striated urethral sphincter and the bladder neck through alpha-adrenergic activity may also play a role in the development of UAB or DU. Treatment of UAB or DU aims to reduce the postvoid residual (PVR) urine volume and increase voiding efficiency, either by spontaneous voiding or abdominal straining. Pharmacotherapy with parasympathomimetics or cholinesterase inhibitors might be tried, and benefits can be achieved in combination with alpha-blockers. Bladder outlet surgeries, including urethral onabotulinumtoxinA injection, transurethral incision of the bladder neck, and transurethral incision or resection of the prostate can effectively improve voiding efficiency and decrease the PVR in most patients with DU. The mechanisms have not been well elucidated. It is likely that ablation of the bladder neck or prostatic urethra might not only decrease bladder outlet resistance but also abolish the sympathetic hyperactivity which inhibits detrusor contractility in patients with idiopathic UAB or DU.